Field‐Induced Inversion of the Magnetoresistive Effect in the Zintl Phase Eu5+xMg18−xSi13 (x=2.2)1. Issue 7 (10th January 2013) - Slabon, Adam; Mensing, Christian; Kubata, Christof; Cuervo‐Reyes, Eduardo; Nesper, Reinhard
<x xml:space="preserve">Abstract</x> Watch the signs! The new Zintl phase Eu5+xMg18−xSi13 (x=2.2) displays a negative as well as a positive magnetoresistive effect depending on the temperature. The maximal value of the magnetoresistivity of 92 % occurs at 100 K and 9 T (see plot).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>